Corrosion Monitoring of Steel Structure Coating Degradation - Bojan Zajec; Mirjam Bajt Leban; Tadeja Kosec; Vili Kuhar; Andraž Legat; Stanislav Lenart; Karmen Fifer Bizjak; Kenneth Gavin (Tehnički Vjesnik, 2018)
An important aspect regarding the sustainability of steel structures is to ensure the structure is protected from corrosion. A number of surface coatings are available that play an important role in protecting these structures. An important part of the management of these structures is reliable and regular inspection along with methods for early detection of corrosion processes. In this paper, a development and application of sensors for monitoring the steel coating degradation and corrosion damage to steel substrate are presented. An encapsulated corrosion kit with integrated EIS sensors and ER probes was developed. To test its efficiency, steel probes were coated with selected coatings in the laboratory and their performance was assessed under various aggressive atmospheres, including; salt, industrial and humid atmosphere.